Transformation of advertising campaigns of sales channels under the influence of digital technologies - E. A. Ponomareva; Yu. V. Vyaltseva (Вестник Северо-Кавказского федерального университета)
Introduction. In the digitalization era, advertising campaigns are also influenced by digital technologies. In this regard, consumer behavior is changing, which manufacturers need to adapt to by resorting to the use of digital marketing tools.Goal. Studying the process transformation of advertising campaigns of sales channels under the influence if digital technologies.Materials and methods. The research was based on scientific works by Russian authors and statistical data. The empirical method of analysis was used in the work. Statistical methods were also used to collect and analyze the necessary information and theoretical methods.Results and discussion. The study was conducted in the basis of statistical data and scientific works of Russian authors. The main trends in the development of advertising campaigns if sales channels were identified. Aspects of personalization, digital marketing tools, and forecasts of e-commerce activity are also analyzed. Conclusion. The results of the study allow the authors to conclude that digital technologies effectively influence the advertising campaigns of sales channels. With their help, companies create the best offers for consumers, as well as provide a wide range of options. It was also noted that online shopping platforms will grow and increase sales in this market.